Embedding neuroscience in psychiatry training. (November 2020) - O'Loughlin, Christopher
SUMMARY: Training in neuroscience is vital to the future of psychiatry as a medical specialty. Trainees and trainers alike demonstrate a desire to keep up to date with developments in the associated scientific fields. Neuroscience increasingly underpins clinical assessments, treatment options and patients' expectations. Psychiatry training in the UK can embrace neuroscience at many levels, from discussing patient presentations with supervisors, to teaching programmes supported by the Royal College of Psychiatrists' activities. Although challenges remain, neuroscience literacy enhances the specialty and will improve patient care.